Knowledge spillovers and the timing of R&D policy - Geir H. Bjertnæs; Tom-Reiel Heggedal; Karl Jacobsen (Statistics Norway, Research Department, 2010)
We analyze how knowledge spillovers influence the optimal timing of R&D policy. Using numerical simulations we find that optimal subsidies to R&D may be rising over time even when the returns to knowledge is decreasing. The optimal time profile of the subsidies is determined by the elasticity of scale in the R&D production function, which again depends on both the returns to knowledge and the returns to labor.
Keywords: O32; O38; 330; Innovation policy; R&D; Technological spillovers